THE REVIEW OF CREATING INTERNATIONALLY RECOGNIZED BRANDS FROM SMALL LOCAL BUSINESSES. - Kumar Garg, Parveen; Kaur, Sandeep (International Journal of Psychosocial Rehabilitation, 2021)
From seeing changes in economy to politics to technological advancements, we see growth in each field. Growing and getting reached is making people fulfill their desires. This study examines the brief detailing of how organizations go global from local. Starting a venture brings a lot of hopes with it, from providing employment to people to making the needs of people fulfilled, making use of resources, and many more. With all this they need development, development in the sense to be RECOGNIZED ACROSS THE GLOBE. For setting up recognition, we need to be perfect all-errands and be ready to accept the upcoming opportunities.